Crafting Personalised Web Interfaces: Enhancing Accessibility for Persons with Disabilities - Macedo, Patricia; Madeira, Rui Neves; Miranda, Paula; Santos, Pedro Albuquerque (International Journal of Online and Biomedical Engineering (iJOE), 2024)
This paper investigates the creation of multimodal web interfaces to foster inclusive services, aiming to empower individuals with disabilities. This paper details the development of SEU (Services to Empower yoU), an online platform designed to improve access to offline services for persons with disabilities through personalised multimodal web interfaces. Developed using a participatory design approach, SEU involved collaboration with Human- Computer Interaction experts, occupational therapists, accessibility experts, and persons with disabilities. The platform supports multiple user needs across cognitive, visual, motor, and hearing impairments. SEU was evaluated in a two-phase usability study, which included expert assessment and testing by persons with disabilities, supplemented with interviews, observations, and questionnaires. Feedback highlighted SEU’s effective design and usability, emphasising its utility in enhancing service accessibility. The study indicates that both experts and persons with disabilities consider the platform an added value. Although the platform was well-received, suggestions for better cognitive support and the addition of a mobile application were noted, acknowledging the regular smartphone usage among the target users.